Pengembangan Model Pembelajaran Teknologi Pengawetan Makanan dengan Mengintegrasikan Modul Pembelajaran di Akademi Tata Boga Bandung - Dwi Wuryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2015)
The purpose is development models in Food Preservation Technology subject of Akademi Tata Boga Bandung.The method research are Borg & Gall and MPI model. Development steps: preliminary research, identifiying instructional needs and and formulating instructional goals, identifying preliminary behavior and characteristic students, formulating specific instructional goals, criterion referenced test,istructional strategy, development, expert review,and formative evaluation. The result of this research is model development with independent instructional module integrated, and lesson plan. Other than that, the research development can improve results from the average score of 74.93 to 87.63, so it is an effective, efficient, and fun learning model